Signs of safety: an investigation of how OHS professionals interpret injury metrics - Pomeroy, James; Pilbeam, Colin (Elsevier, 2025)
Introduction: Injury metrics are traditional indicators of safety performance widely used by organizations, industry bodies, and regulatory agencies. In this paper we contend that they are semiotic signs leading to a variety of interpretations beyond their traditionally held meaning as a representation of an organization's safety performance. We argue that injury metrics are semiotic signs where different organizational uses and signals lead to a variety of interpretations amongst internal and external stakeholders. Method: This exploratory study reveals these different uses and meanings through semi-structured interviews with 20 experienced occupational health and safety professionals from around the world. Through the uses of injury metrics that they described, we identified 17 separate and distinct meanings that signify four different objects of the injury metric, namely management control, image management, risk measurement, and trust in leadership. Results: The findings demonstrate that the meaning of injury metrics is not singular but is contingent and contextually determined. With multiple meanings, a decreasing injury metric is not necessarily a sign of improving safety. It is suggested that injury metrics may support ‘safety work’ by OHS professionals and that they may have unintended consequences that are antithetical to safety in the workplace. Practical applications: Given the role of injury metrics in indicating the safety of an organization, these findings have practical implications for the reliance placed on them and the inferred meanings.
Keywords: 3505 Human Resources and Industrial Relations; 35 Commerce, Management, Tourism and Services; Logistics & Transportation; 3509 Transportation, logistics and supply chains; 4206 Public health; Safety indicators; Semiotics; Safety Professionals; Unintended consequences; Meaning-making